2010
DOI: 10.1245/s10434-010-1087-z
|View full text |Cite
|
Sign up to set email alerts
|

Impact of US Surveillance on Detection of Clinically Occult Locoregional Recurrence after Mastectomy for Breast Cancer

Abstract: LRUS during breast US after mastectomy for breast cancer was helpful for the early detection of recurrence and may lead to a better prognosis for patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
39
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(39 citation statements)
references
References 43 publications
0
39
0
Order By: Relevance
“…In recent years, the effectiveness of breast ultrasound was reported for the purpose of the diagnosis of breast cancer recurrence. Kim et al (2010) observed that breast ultrasound was a useful method for the diagnosis of cancer recurrence in patients without clinical symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, the effectiveness of breast ultrasound was reported for the purpose of the diagnosis of breast cancer recurrence. Kim et al (2010) observed that breast ultrasound was a useful method for the diagnosis of cancer recurrence in patients without clinical symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have shown surveillance results of US applied to women who were treated for breast cancer (34, 37, 39, 40, 41). The reported cancer detection rates were 1.7-5.1% per patient, and the positive predictive value (PPV) was 21.5-52.6%, with percentages varying according to the area involved.…”
Section: Imaging Modalitiesmentioning
confidence: 99%
“…The reported cancer detection rates were 1.7-5.1% per patient, and the positive predictive value (PPV) was 21.5-52.6%, with percentages varying according to the area involved. Because isolated recurrences are associated with distant metastasis and/or poor outcome, early detection and targeted treatment for recurrences are critical to improve patient outcome (41, 42, 43). Early detection of a locoregional recurrence of breast cancer after primary treatment by US can help guide patient management by sorting out those who may benefit by early therapeutic intervention or curative treatment of local disease.…”
Section: Imaging Modalitiesmentioning
confidence: 99%
“…Kim et al [3] studied the LRR with US in 874 asymptomatic patients treated with mastectomy for BC. During a mean follow-up of 37 months the Authors found 22 suspicious lesions that were histologically confirmed in 6 cases.…”
Section: Accuracy Of Us Examination In Bc Follow-upmentioning
confidence: 99%
“…The risk of LRR is related to the clinical staging and it is considered as an independent risk factor for distant metastasis and death; an early diagnosis in patients clinically negative could have a positive impact on survival compared to symptomatic patients [2,3].…”
Section: Introductionmentioning
confidence: 99%